CULTURAL HYBRIDITY TOWARDS AN UPWARD MOBILITY: IMPLICATIONS OF THE AMERICAN MEDIA AND AMERICAN CORPORATE CULTURE IN INDONESIA - Alfred Inkiriwang; Riani E. Inkiriwang Winter (Rubikon : Journal of Transnational American Studies, 2014)
Hybridity has been defined in many terms. Subsequently, cultural hybridity is associated with different meanings, as seen from a spectrum of theoretical and disciplinary perspectives. In the realm of Transnational American Studies in Indonesia, the hybridization of American Media and American Corporate Culture into those domains in Indonesia would be an observable transnational cultural phenomenon. American corporate culture has a hegemonic dominance in the world as it has in Indonesia. Similarly, in the current global media culture, American media’s influence has brought with it its culture to places throughout the world including Indonesia. In the current discourses hybridity has “long left behind the negative implications and connotations of inferiority” and it presents currently the intercultural exchange of transnational and global mobility. This article explores American and Indonesian cultural hybridity as a notion of upward mobility in the domain of media culture and corporate culture in Indonesia.